HUBUNGAN KEKUATAN OTOT TUNGKAI DENGAN KETEPATAN SHOOTING KE ARAH GAWANG DALAM PERMAINAN SEPAKBOLA SISWA EKSTRAKURIKULER SMP DA’WAH PEKANBARU - Ferdi Erwansyah; Ramadi '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on examination of junior high school students Da'wah Pekanbaru that shooting soccer players who follow the practice is still not good, it is known that the knowledge of the basic techniques of football players is still relatively low and low physical condition also affects the shooting, but the basic technique and physical condition is a technique that must be mastered by a soccer player. to know about the relationship between leg muscle strength with precision-kick towards goal football at junior high student extracurricular Da'wah Pekanbaru. The population in this study throughout the research object, the junior soccer team soccer player Da'wah Pekanbaru, consisting of 18 people. Sampling using total sampling so that the sample is 18 people. The instrument is used to measure kekeuatan Dysnamometer Leg leg muscle and test shooting (Shooting). Data collected was analyzed by using correlation produc moment. Based on the results of research that has been described in the previous chapter, it can be concluded that the results obtained from leg muscle strength has a significant connection with the shooting on goal in a game of football at junior high school student extracurricular Da'wah Pekanbaru. This is evident from analysis results obtained by the rhitung> rtabel at α = 0.05.Keywords: Limb Muscle Strength, Accuracy kick